Arabidopsis 22-Kilodalton Peroxisomal Membrane Protein. Nucleotide Sequence Analysis and Biochemical Characterization - Tugal, H. Bülent (American Society of Plant Physiologists, 1999)
We sequenced and characterized PMP22 (22-kD peroxisomal membrane protein) from Arabidopsis, which shares 28% to 30% amino acid identity and 55% to 57% similarity to two related mammalian peroxisomal membrane proteins, PMP22 and Mpv17. Subcellular fractionation studies confirmed that the Arabidopsis PMP22 is a genuine peroxisomal membrane protein. Biochemical analyses established that the Arabidopsis PMP22 is an integral membrane protein that is completely embedded in the lipid bilayer. In vitro import assays demonstrated that the protein is inserted into the membrane posttranslationally in the absence of ATP, but that ATP stimulates the assembly into the native state. Arabidopsis PMP22 is expressed in all organs of the mature plant and in tissue-cultured cells. Expression of PMP22 is not associated with a specific peroxisome type, as it is detected in seeds and throughout postgerminative growth as cotyledon peroxisomes undergo conversion from glyoxysomes to leaf-type peroxisomes. Although PMP22 shows increased accumulation during the growth of young seedlings, its expression is not stimulated by light.